Neuro-fuzzy-based hand-off and opportunistic spectrum access for cognitive cooperative network. (1st January 2012) - Kaiser, M.S.; Ahmed, K.M.
This paper investigates neuro-fuzzy (NF)-based opportunistic spectrum access and spectrum hand-off (HO) for a cognitive cooperative network (CCN). The main aim is to increase the average throughput of the CCN. Secondary users (SUs) in the CCN are scheduled using α-proportional scheduling. The NF α-based algorithm enables each SU to determine the most appropriate channel for its data transmission. SUs keep their transmission power below the interference temperature through power control and do not interfere with the normal operation of primary radio network (PRN). If the quality of service (QoS) of the SU is not obtained, a HO occurs. Mamdani-adaptive neuro-fuzzy inference system (M-ANFIS) is used to construct spectrum access and HO controllers. The proposed algorithm is compared with the existing algorithms. Performance evaluations clearly reveal that the outage probability is reduced and average throughput of the CCN is increased.